Does laparoscopic treatment of deep endometriosis improve sexual dysfunction - Abolfazl Mehdizadehkashi; Shahla Chaichian; Samaneh Rokhgireh; Kobra Tahermanesh; Shahla Mirgaloybayat; Reza Saadat Mostafavi; Sepideh Khodaverdi; Marziyeh Ajdary; Mahin Ahmadi Pishkuhi (Babol University of Medical Sciences, 2023)
Background: Endometriosis is one of the common gynecological problems during the reproductive years, affecting the quality of life, fertility, and sexual function of women. It is known that sexual dysfunction and quality of life are interrelated. Therefore, this study aimed to evaluate the effect of resection of endometriosis lesions via laparoscopic surgery on the improvement of sexual dysfunction in women with endometriosis. Methods: This clinical trial was performed on 30 patients with endometriosis. The Female Sexual Function Index, Endometriosis Health Profile-30, and Visual Analog Scale were completed for the patients before laparoscopic surgery and three, six, and 12 months after surgery. The results were examined and compared before and after the intervention using the ANOVA test. Results: The present results showed that the mean pain score of the patients (dysmenorrhea, dyspareunia, and pelvic pain) was significant after laparoscopic surgery (P<0.005). The female sexual function improved after laparoscopic surgery compared to the preoperative phase, and changes in the domains of psychological stimulation, humidity, and sexual orgasm were significant (P<0.005). Moreover, the female quality of life scores increased in all dimensions compared to the preoperative phase, although these improvements were not statistically significant. Conclusion: The present results revealed that laparoscopic surgery is an effective treatment, leading to a considerable improvement in female sexual function.